CORRELATOS ELETROFISIOLÓGICOS DE MODIFICAÇÕES DA ATENÇÃO EM LONGO PRAZO - Pasquini, Henrique Adam (2013)
Attention is probably one of the oldest theoretical constructs in Psychology. In the Eastern countries, meditation has been seen as a group of technics that goals to train people to focus attention. This research aims to check its electrophysiological correlates, taking into consideration the long term changes accompanying regular practice of meditation. We have used modern technics of high resolution electroencephalography analyze slow potentials, power in various bands, and event-related band-power. We recorded the EEG using a 128-channel montage, in 31 subjects (17 meditators). We analyzed the type of meditation related to a Zen Buddhist practice of the Soto school, which belongs to the group of mindfulness meditation. The goal of the research was to verify if the power on the beta band would rise. However, not quite what we expected, no significant changes were detected on the beta band. On the other hand, the main finding of this research was that the weekly practice of meditation is associated with a rise in the induced relative theta band power, an increase in the ratio of induced power (theta/beta), and an increase in the ratio of the induced relative band power (theta/beta), which occurred during an adapted meditation task. We also noticed that the practice of meditation was related to a decrease of the alpha peak frequency during the task of focused attention. We discuss the decrease of the alpha peak frequency with respect to the hypothesis of brain efficiency. On the other hand, the increase of the induced relative theta band power and of the ratio of theta/beta induced power bands, during the adapted meditation task, suggests that the plain attention type of meditation is rather related to a deliberate loss of attention, by the permissive distractions of the meditators.